International exchange of information in tax matters : towards global transparency - Oberson, Xavier, 1961-; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2018)
In this updated second edition, Xavier Oberson provides an authoritative overview of the instruments and models used to exchange information in tax matters on an international level. This book addresses the latest developments in the movement towards increased global transparency in tax matters and highlights how various international models interact. Key features of the second edition include: Analysis of the OECD common reporting standard of automatic exchange of information; definition of the various rights, substantial and procedural, that can be used during different phases of information exchange; discussion on a range of international instruments and models including: double taxation treaties, TIEAs, the OECD multinational convention, European Directives, FATCA and the Swiss Rubik model; examination of the impact of the OECD Base Erosion and Profit Shifting (BEPS) Program. Lawyers and tax specialists looking to further their knowledge will find this book to be an invaluable reference. Professionals in banking and finance will find this to be an informative read. Students and academics in law, tax and economics will appreciate the clear overview and find many useful insights.
1. General introduction -- 2. Historical development of international exchange of information rules -- 3. Exchange of information under Double Taxation Conventions (DTC) -- 4. A practical example: administrative assistance and exchange of information between the United States and Switzerland -- 5. Assistance in the collection of taxes under DTC -- 6. Tax Information Exchange Agreements (TIEAs) -- 7. The OECD Convention on Mutual Administrative Assistance in Tax Matters (CMAAT) -- 8. The EU directives -- 9. The so-called Swiss 'Rubik' agreements -- 10. Foreign Account Tax Compliance Act (FATCA) -- 11. Towards automatic exchange of information -- 12. Automatic exchange of information (AEOI): the OECD common reporting standard -- 13. Solving the past -- 14. The impact of the BEPS programme -- 15. Legal protection of the taxpayer -- 16. Conclusion -- General bibliography -- Index.
Obsahuje bibliografii, bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: daně; taxation; e-knihy online; e-books online